The diversity of life - Wilson, Edward O. (New York : W.W. Norton, 1993)
"In this book a master scientist tells the great story of how life on earth evolved. Edward O. Wilson eloquently describes how the species of the world became diverse, and why the threat to this diversity today is beyond the scope of anything we have known before." "The Diversity of Life has quickly become a classic text in its definition of a new environmental ethic - our obligation to rescue ecosystems, not simply individual species - and its prescient call for an end to the conservation versus development argument. In an extensive new foreword for this edition, Professor Wilson addresses the explosion of the field of conservation biology and takes a clear-eyed look at the work still to be done."--BOOK JACKET.
Keywords: Biodiversity; Biodiversity conservation